Lumped surface and sub-surface runoff for erosion modeling within a small hilly watershed in northern Vietnam - Bui, Y.T.; Orange, Didier; Visser, S.M.; Hoanh, Chu Thai; Laissus, M.; Poortinga, A.; Tran, D.T.; Stroosnijder, L. (Wiley, 2013)
Developing models to predict on-site soil erosion and off-site sediment transport at the agricultural watershed scale represent an ongoing challenge in research today. This study attempts to simulate the daily discharge and sediment loss using a distributed model that combines surface and sub-surface runoffs in a small hilly watershed (< 1km2). The semi-quantitative model, Predict and Localize Erosion and Runoff (PLER), integrates theManning-Strickler equation to simulate runoff and the Griffith University Erosion System Template equation to simulate soil detachment, sediment storage and soil loss based on a map resolution of 30m 30m and over a daily time interval. By using a basic input data set and only two calibration coefficients based, respectively, on water velocity and soil detachment, the PLER model is easily applicable to different agricultural scenarios. The results indicate appropriate model performance and a high correlation between measured and predicted data with both Nash-Sutcliffe efficiency (Ef) and correlation coefficient (r2) having values>0.9. With the simple input data needs, PLER model is a useful tool for daily runoff and soil erosion modeling in small hilly watersheds in humid tropical areas.